Labour's First Year : 1945-46 (London : Common Wealth Publications Committee, 1946)
1946 1946 1940s 27 pages Did This Pamphlet Interest You ? If so, read FOREIGN AFFAIRS Conflict or Co-operation? 3d. U.N.O. — Can it Succeed? 1d. The German Problem (H.N. Brailsford) 3d. DEMOCRACY Man Must Be Free 6d. The Soldier as a Citizen 6d. Representative Government 4d. INDUSTRY Coal — Can the New Act Succeed? 1d. Nationalisation is not Socialism! 6d. The Missing Tool — Democracy 1d. GENERAL Common Wealth, 1946 ... ... ... ... 2d. Challenge of our Principles 6d. Seven Pillars of Peace (Olaf Stapledon) 3d. and of course, Common Wealth Review — Monthly — 6d. From : COMMON WEALTH 44, BLOOMSBURY STREET, LONDON, W.C.1 15X/2/98/21